A Portfolio of Platform Cooperativism, in Progress - Scholz, Trebor (Ökologisches Wirtschaften - Fachzeitschrift, 2019)
Today, the power asymmetry between those who own the World Wide Web’s core platforms and the users who depend on them is more pronounced than ever. A decentralized digital economy is needed that is built on broad-based ownership and democratic governance. Platform Cooperativism could be an answer.